Endemic climbing cavy Kerodon acrobata (Rodentia: Caviidae: Hydrochoerinae) from dry forest patches in the Cerrado domain: new data on distribution, natural history, and morphology - Bezerra, Alexandra M. R.; Bonvicino, Cibele R.; Menezes, Albert A. N.; Marinho-Filho, Jader (Zootaxa, 2010)
The distribution, natural history, and morphology of Kerodon acrobata were updated based on nine new collected specimens totalling 14 known specimens. Two new localities were added to the distribution range of this species. Data on habitat use indicated that the presence of this rodent is associated to the cerrado sensu stricto and seasonally dry tropical forest patches in the northeastern Cerrado domain. Analyses of these specimens increased the range of body size and craniodental measurements for K. acrobata. We also describe, for the first time, phallic morphology of K. acrobata which exhibits a subcylindral glans penis and a simple baculum. High hunting activity and continuous loss of its natural habitat are factors that can be negatively affecting its populations. Habitat replacement poses a likely risk the present diversity at seasonally dry tropical forest enclaves of the northeastern Cerrado domain.